DNA barcodes unite two problematic taxa: the meiobenthic Boreohydra simplex is a life-cycle stage of Plotocnide borealis (Hydrozoa: Aplanulata) - Pyataeva, Sofia V.; Hopcroft, Russell R.; Lindsay, Dhugal J.; Collins, Allen G. (Zootaxa, 2016)
Genetic barcodes of arctic medusae and meiobenthic cnidarians have uncovered a fortuitous connection between the medusa Plotocnide borealis Wagner, 1885 and the minute, mud-dwelling polyp Boreohydra simplex Westblad, 1937. Little to no sequence differences exist among independently collected samples identified as Boreohydra simplex and Plotocnide borealis, showing that the two different forms represent a single species that is henceforth known by the older name Plotocnide borealis Wagner, 1885. The polyp form has been observed to produce bulges previously hypothesized to be gonophores, and the results here are consistent with that view. Interestingly, the polyp has also been reported to produce egg cells in the epiderm, a surprising phenomenon that we document here for only the second time. Thus, P. borealis produces eggs in two different life stages, polyp and medusa. This is the first documented case of a metagenetic medusozoan species being able to produce gametes in both the medusa and polyp stage. It remains unclear what environmental/ecological conditions modulate the production of eggs and/or medusa buds in the polyp stage. Similarly, sperm production, fertilization and development are unknown, warranting further studies.